Prosthodontic presurgical treatment of midline facial cleft in West syndrome infant - Dewi Vindani; Lisda Damayanti; Helmi Siti Aminah; Nitami, Detin (Indonesia Prosthodontic Association, 2024)
Background: Midline facial cleft is extremely rare congenital malformation. It may be associated with other syndromes, including West syndrome (WS), a severe form of epilepsy in infancy. Objective: This report presents modified Presurgical Nasoalveolar Molding (PNAM) treatment of midline facial cleft in WS patient. Case Report: An infant girl born with midline facial cleft, characterized by flat nose due to complete absence of nasal cartilage, columella, and premaxilla. She was also diagnosed with WS, hydrocephalus, and cerebral palsy. PNAM treatment was performed, consisting of feeding plate and extraoral nasal hook. The feeding plate prevented tongue protrusion which could interfere the airway during multiple spasms and trained her to place the tongue in its normal position. The extraoral strapping was retracted across the upper lip and feeding plate was grinded selectively to approximate the lip and alveolar segment concurrently. An elastic band was paired on nasal hook and attached to the forehead to elevate nasal dome and maintain the airway during retraction. After 1 year follow-up, alveolar gap was reduced by 4,5mm, lip segment moved closer to the midline, and bodyweight increased sufficiently. Conclusion: Modified PNAM can help infant with WS breath, increase nutritional intake and mold the alveolar tissue properly. Keywords: midline facial cleft, West syndrome, modified PNAM